Elements of the Anthropological Theory of Didactics in the Selection of Contents in a Course of Fluid Mechanics in Engineering - José Luis Díaz Palencia; Antonio Naranjo Redondo; Pedro Vivas Caballero (International Journal of Engineering Education, 2022)
The Anthropological Theory of Didactics has been applied to the field of didactics of mathematics with remarkable success. Fluid Mechanics is a discipline with a strong mathematical background, where mathematics is used for modeling the continuous environment. In addition, the Fluid Mechanics concepts are essential for the future engineer or scientist. For this reason, it is worth thinking whether the content that developed in engineering schools or science faculties are those demanded by the future professionals. The objective of this article is to know the institutional distance between the University and society as a demander of technologies based on Fluid Mechanics. To this end, the methodology based on the issuance of a questionnaire to experts focused on aspects such as present and emerging content associated with the Fluid Mechanics of an engineering degree is used. The results highlight the existence of an institutional distance between the University and the Enterprise (as a technology executor) in the conception of contents, thus establishing an area of potential improvement within the noosphere associated with fluid mechanics.